Inkjet printed organic and perovskite photovoltaics—review and perspectives - Maisch, Philipp; Tam, Kai Cheong; Jang, DongJu; Steinberger, Marc; Yang, Fu; Brabec, Christoph; Egelhaaf, Hans-Joachim (Organic Flexible Electronics, 2021)
This chapter provides a review on digital printing of organic solar cells (OSCs) and perovskite solar cells (PSCs). It starts with a brief introduction to the fundamentals of both solar technologies. Highlighting the specific demands of many novel solar applications, the necessity to fabricate devices using cheap and most versatile techniques, such as drop-on-demand inkjet, is outlined. A short discussion on the fundamentals of inkjet technology provides the background for a literature overview on digitally printed OSCs and PSCs. The main part of this chapter describes the most significant achievements in the field and remaining challenges for inkjet fabrication of active layers, electron- as well as hole-transport layers and electrodes. An outlook on the perspectives that the combination of printed photovoltaics and inkjet has to offer concludes the chapter.<br
Keywords: Inkjet; organic photovoltaics; OPV; OSC; perovskite photovoltaics; PSC; printed solar cell; solar module; flexible electrode